Challenges and Opprotunities of Halal Certification Bodies in Building a Halal Ecosystem - Mohammad Ridwan; Siti Nur Mahmudah; Muhammad Habibie (Niqosiya: Journal of Economics and Business Research, 2026)
Introduction: This study explores the structural, human resource, and operational challenges experienced by Halal Inspection Bodies (LPH) within Indonesian Islamic universities, with a particular focus on UIN Ponorogo and UIN Kediri. Research Methods: This research employs a structured literature review to synthesize findings from scholarly publications, regulatory documents issued by BPJPH, technical guidelines on halal assurance, and national as well as international studies on halal governance. Through thematic analysis of the collected literature, four central issues are identified: inconsistent regulatory updates from BPJPH, limited availability of certified auditors, low MSME readiness in fulfilling documentation and traceability requirements, and recurring technical disruptions in the SiHalal digital system. Results: Despite these challenges, several enabling factors emerge, including increasing public awareness of halal assurance, supportive local government initiatives, and the expanding strategic role of university-based halal centers. Conclusion: This study argues that harmonizing regulatory procedures, improving digital infrastructure, strengthening auditor development programs, and enhancing cross-sector collaboration are essential steps toward building an effective and sustainable national halal ecosystem.